ANALYSIS OF COMPARISON OF BANKRUPTCY PREDICTION ABILITY BETWEEN ALTMAN Z-SCORE ANALYSIS AND ZMIJEWSKI X-SCORE ANALYSIS IN FINANCIAL SERVICES COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2017-2021 PERIOD - Shinta Novitalia; Chairil Akhyar; Adnan; Jumaini (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to determine the comparative analysis of bankruptcy predictive ability between the Altman z-score and Zmijewski x-score analyses of financial services companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This study uses secondary data in the form of financial statements of each financial service company, where the sample used in this study is 41 financial service companies listed on the Indonesia Stock Exchange. The data analysis method used is the Altman z-score and Zmijewski x-score models with the help of Microsoft Excel 2019 software. The results of the study reveal that (1) from the results of the Altman Z-Score, it is obtained that as many as 19 companies are predicted to experience bankruptcy within five years of the study period, while 6 financial services companies are predicted not to go bankrupt during the five years of the study period. (2) Zmijewski's analysis shows that 3 financial service companies are predicted to go bankrupt during the five-year study period, and 29 financial service companies are predicted not to go bankrupt during the five-year study period. (3) The results of calculating the level of accuracy found that the Altman Z-Score model is the best in predicting the bankruptcy of financial services companies with an accuracy rate of 68.78%, while the Zmijewski model only obtains an accuracy rate of 16.09%.